Antimicrobial stewardship in companion animal practice: an implementation trial in 135 general practice veterinary clinics. Issue 1 (25th February 2022) - Hardefeldt, L. Y.; Hur, B.; Richards, S.; Scarborough, R.; Browning, G. F.; Billman-Jacobe, H.; Gilkerson, J. R.; Ierardo, J.; Awad, M.; Chay, R.; Bailey, K. E.
Abstract: Background: Antimicrobial stewardship programmes (ASPs) have been widely implemented in medical practice to improve antimicrobial prescribing and reduce selection for multidrug-resistant pathogens. Objectives: To implement different antimicrobial stewardship intervention packages in 135 veterinary practices and assess their impact on antimicrobial prescribing. Methods: In October 2018, general veterinary clinics were assigned to one of three levels of ASP, education only (CON), intermediate (AMS1) or intensive (AMS2). De-identified prescribing data (1 October 2016 to 31 October 2020), sourced from VetCompass Australia, were analysed and a Poisson regression model fitted to identify the effect of the interventions on the incidence rates of antimicrobial prescribing. Results: The overall incidence rate (IR) of antimicrobial prescribing for dogs and cats prior to the intervention was 3.7/100 consultations, which declined by 36% (2.4/100) in the implementation period, and by 50% (1.9/100) during the post-implementation period. Compared with CON, in AMS2 there was a 4% and 6% reduction in the overall IR of antimicrobial prescribing, and a 24% and 24% reduction in IR of high importance antimicrobial prescribing, attributable to the intervention in the implementation and post-implementation periods, respectively. A greater mean difference in the IR of antimicrobial prescribing was seen in high-prescribing clinics. Conclusions: These AMS interventions had a positive impact in a large group of general veterinary practices, resulting in a decline in overall antimicrobial use and a shift towards use of antimicrobials rated as low importance, with the greatest impact in high-prescribing clinics.